Bordering Binarities and Cognitive Cartography: What on Earth Does Literature Have to do with Border Transactions? - Moi, Ruben (Nordlit, 2009)
Although literature and poetry have numerous borders of their own,these are rarely assumed to have any significance for the world out-side the text itself. A number of reasons for this distinctive division certainly stem from the literary field itself. This paper intends to indicate the exclusivist stance of some theories of literature, and the inclucivist of others, before exploring the possibilities of bridging between borders in text and territory by reference to the life and literature of Oscar Wilde and a performative and imaginative analysis of Paul Muldoon's epigrammatic poem The Plot.